The Use of Board Game to Improve Students’ Writing Skill of the Descriptive Text at SMPN 18 Surabaya - Rukiyah Rukiyah (STKIP PGRI SIDOARJO, 2020)
The study examined the implementation of board games through the students’ achievement in writing skill through descriptive text at SMPN 18 Surabaya. It used the pre-test post-test design in classroom action research model for the students in class VIII-G as subjects selected from sampled classes. T-test was used as the statistical technique for the data analysis. The hypotheses were tested at 0.05 level of significance. The results showed the data in the tables t-Test: Paired Two Sample for Means (VIII-G) reveal that the obtained t-value was -10.83171521 which were well above the limit of 0.05 of significance. The post-test had a higher mean of 80.39473684. While the pre-test had a mean of 69.36842105. Because p-value (4.97263E-13) was less than the standard significance level of 0.05, researchers can reject the null hypothesis (Ho). Thus, the second hypothesis (Ha) was accepted regarding there is significant effect of the implementation of board games through the students’ achievement in writing skill through descriptive text. It is hereby recommended that English teachers should adapt this model to enhance students’ achievement in other English skills. For students, it is suggested they have to be more paying attention to the model of teaching being applied such as the implementation of board games through the students’ achievement in writing skill through descriptive text so they can be able to explore their skill of writing as well. Other researches, however, should explore to investigate the effect of other games on specific writing genres.